내측 반월상 연골판 후방 골 기시부 파열의 관절경적 봉합술 후 내시경적 추시 결과 - 김성우(Sung-Woo Kim); 성민규(Min-Kyu Sung); 최정윤(Jung-Yun Choi) (The journal of the Korean Orthopaedic Association, 2014)
Purpose: The purpose of this study is to evaluate the healing rate of medial meniscus root repair according to the duration of symptom and to determine the association between healing status and the clinical result after medial meniscus root repair. Materials and Methods: Eighty-four patients who underwent arthroscopic meniscal root repair and second-look arthroscopy were included. Second-look arthroscopy evaluation of meniscal healing status was performed by dividing medial meniscal posterior root into the anterior half and posterior half and classifying by contact degree on the surface of the tibia and continuity. Clinical results were analyzed according to International Knee Documentation Committee (IKDC) subjective scores and Lysholm scores. In addition, after dividing cases according to acute group and chronic group by six-month symptomatic period, differences were evaluated. Results: Significant differences in post-operative clinical results were observed between the acute group and chronic group. A significant difference in meniscal healing status was observed between the two groups (p<0.001). A higher postoperative IKDC score and Lysholm score was observed for the completely healed group, as confirmed by second-look arthroscopy, than for the other groups. Conclusion: In the aspect of improving the clinical result, arthroscopic medial meniscal posterior root repair is a good treatment modality. Early repair of medial meniscal posterior root may lead to improvements in the clinical result such as meniscal healing status. KCI Citation Count: 1